Use of Chicory (Cichorium intybus L.) Root for the Treatment of Intractable Hiccups - Qadir Mohammadi; Mohammad Bagher Minae; Mohammad Somi; Mahmoud Mosaddegh; Mohammad Kamalinejad (Traditional and Integrative Medicine, 2016)
Although hiccups may be a temporary action which need no treatment, sometimes a refractory hiccup would be disturbing to a normal life. In such cases, an underlying etiology is often present, and may be overlooked. One the important etiology claimed in Iranian traditional medicine for intractable hiccups is liver diseases. In this study, management of intractable hiccups by chicory in two cases with the liver obstruction has been presented.